2013
DOI: 10.1186/1753-2000-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diagnostic stability of ADHD and ODD in Turkish children: a 4-year longitudinal study

Abstract: BackgroundThis study was designed to assess the prevalence of Attention-Deficit/Hyperactivity Disorder (ADHD) and Oppositional Defiant Disorder (ODD) in a representative sample of second grade students from a country in a region where no previous rates are available (Turkey). The second aim is to evaluate the differences in ADHD and ODD prevalence rates among four different waves with one-year gap in reassessments.MethodSixteen schools were randomly selected and stratified according to socioeconomic classes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 42 publications
8
34
3
5
Order By: Relevance
“…Our results demonstrated that the prevalence of ADHD in the control group was not different than the recent epidemiological data of Turkey 13 .…”
Section: Discussioncontrasting
confidence: 65%
“…Our results demonstrated that the prevalence of ADHD in the control group was not different than the recent epidemiological data of Turkey 13 .…”
Section: Discussioncontrasting
confidence: 65%
“…Although this rate is markedly higher than the 5.9% reported by a worldwide meta-analysis of ADHD prevalence, 14 it is within the range that has been reported for ADHD prevalence 9 as well as that of epidemiological studies conducted in Turkey, 21,30 and Chile. 31 Although no similar studies have been reported from the TRNC to date, our methodology and results are in close agreement with studies of Turkish children from Turkey, such as the epidemiological study reported by Ercan et al 30 from the İzmir province of Turkey, which used a very similar method-logy and reported a prevalence of 13.6%. Two other epidemiological studies, one by Ercan et al 21 another by Rowland et al 9 reported highly similar results to ours, 12.7% and 12.9% respecttively.…”
Section: Discussionmentioning
confidence: 44%
“…The case was considered to be impaired if he/she was rated as very problematic in at least one area or a little problematic in two or more areas. Similar approaches were previously used in epidemiologic studies [14,31,32].…”
Section: Diagnostic Proceduresmentioning
confidence: 93%
“…Recently, our group conducted a developmental epidemiology study to fill this gap in the literature [14]. This study was a 4-year longitudinal investigation on the ADHD and ODD prevalence rates conducted in Turkey which is an interesting geographical area standing on the intersection of Europe, Asia, and Middle East.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation